Estimating the Impacts of Radiation Belt Electrons on Atmospheric Chemistry Using FIREBIRD II and Van Allen Probes Observations. Issue 7 (31st March 2021) - Duderstadt, K. A.; Huang, C.‐L.; Spence, H. E.; Smith, S.; Blake, J. B.; Crew, A. B.; Johnson, A. T.; Klumpar, D. M.; Marsh, D. R.; Sample, J. G.; Shumko, M.; Vitt, F. M.
Abstract: This study considers the impact of electron precipitation from Earth's radiation belts on atmospheric composition using observations from the NASA Van Allen Probes and NSF Focused Investigations of Relativistic Electron Burst Intensity, Range, and Dynamics (FIREBIRD II) CubeSats. Ratios of electron flux between the Van Allen Probes (in near‐equatorial orbit in the radiation belts) and FIREBIRD II (in polar low Earth orbit) during spacecraft conjunctions (2015–2017) allow an estimate of precipitation into the atmosphere. Total Radiation Belt Electron Content, calculated from Van Allen Probes RBSP‐ECT MagEIS data, identifies a sustained 10‐day electron loss event in March 2013 that serves as an initial case study. Atmospheric ionization profiles, calculated by integrating monoenergetic ionization rates across the precipitating electron flux spectrum, provide input to the NCAR Whole Atmosphere Community Climate Model in order to quantify enhancements of atmospheric HO x and NO x and subsequent destruction of O3 in the middle atmosphere. Results suggest that current APEEP parameterizations of radiation belt electrons used in Coupled Model Intercomparison Project may underestimate the duration of events as well as higher energy electron contributions to atmospheric ionization and modeled NO x concentrations in the mesosphere and upper stratosphere. Plain Language Summary: High‐energy particles precipitating into the atmosphere from space affect the chemistry and composition of Earth's atmosphere. While there is significant understanding about the atmospheric impacts of auroral electrons, solar protons, and galactic cosmic rays, the effects of electrons from the near‐Earth Van Allen radiation belts remain uncertain. This study helps quantify electrons precipitating into the atmosphere by comparing measurements within the radiation belts from the NASA Van Allen Probes spacecraft to observations from the low‐altitude NSF Focused Investigations of Relativistic Electron Burst Intensity, Range, and Dynamics (FIREBIRD II) CubeSats. Global atmospheric model simulations quantify the impact of estimated electron precipitation on the ionization and chemical composition of Earth's atmosphere. Results from an initial case study using this new method suggest that electrons from the radiation belts may produce more atmospheric ionization at lower altitudes and for longer duration than currently recommended estimates, potentially affecting the chemistry of ozone in the middle atmosphere and as a consequence influencing atmospheric heating and dynamics. Key Points: Conjunctions between Van Allen Probes and FIREBIRD II enable novel estimates of atmospheric electron precipitation Estimates of electron precipitation from Van Allen Probes suggest CMIP6 may underestimate atmospheric ionization from 60 to 70 km Direct production of NO x by precipitating electrons during March 2013 using this new method suggest 40% enhancements from 60 to 70 km